PEDAGOGICAL KNOWLEDGE IN THE CONTENT OF PEDAGOGICAL PREPARATION OF FUTURE TEACHERS - Kondrashova, L.V. (Pedagogy of Higher and Secondary Education, 2006)
The necessity of including of different pedagogic knowledge in the content of pedagogic training of students o f pedagogic university and its structuring on the base of different approached is proved.